Rigged against them: women camera operators at the BBC during the 1970s and 1980s. Issue 4 (7th June 2022) - Baker, Jeannine; Hall, Nick
ABSTRACT: In 1973, in response to pressure from trade unions and women's groups, and a damning report that exposed the discriminatory policies and attitudes underpinning women's employment, the British Broadcasting Corporation (BBC) committed to the recruitment of women into previously male-only technical occupations. This article examines draws upon public and private archives, and oral history interviews with former BBC women film and television camera operators, to assess the extent to which the Corporation's commitment to equality brought about sustained change to women's opportunities in technical areas of television. Although stereotypical assumptions about women's technical ability proved unfounded, women's employment in camera roles continued to be restricted through recruitment policies and procedures that favoured male applicants. Women's entry into technical areas also challenged existing gendered power relations and workplace culture within television studios. The BBC's inadequate commitment to meaningful change to discriminatory work practices further entrenched the equation of technical skill with masculine labour.